Nowa ekonomia instytucjonalna jako narzędzie analizy i implementacji zasad zrównoważonego rozwoju - Platje, Joost (New institutional economics as an instrument for analysing and achieving sustainable development, 2007)
The aim of this article is to create a theoretical basis for extending New Institutional Economics (NIE) from a theory which often focuses on the economic effects of institutions to a theory that is useful in analyzing and implementing principles of sustainable deyelopment. The author presented a theoretical model of NIE in the context of sustainable deyelopment. Furthermore, he discussed the importance of property rights and an institutional eąuilibrium (where informal institutions support and strengthen formal institutions) for the deyelopment of institutional Capital as a condition for sustainable deyelopment.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 65-78